1997
DOI: 10.1086/514054
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Modulation of Early Virologic and Immunologic Events during Primary Simian Immunodeficiency Virus Infection in Rhesus Monkeys

Abstract: Virologic and immunologic effects of immunomodulation during primary simian immunodeficiency virus (SIV) infection were examined in monkeys treated with cyclosporin or vehicle for 32 days beginning 5 days before SIV inoculation. Duration of antigenemia decreased in 5 of 7 treated monkeys, 2 having delayed onset and peak of antigenemia. Although proviral DNA levels in blood and lymph nodes and infected cell numbers in lymph nodes were transiently decreased, levels were similar to those in controls by day 14. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…17 The primary concern is the potential side effects of immunosuppression after OLT and the effect it may have on HIV disease progression. [18][19][20][21][22][23][24] The conceptual conflict lies in the iatrogenic immunosuppression of an already immunosuppressed individual (i.e., an HIV-positive patient). Early reports, before the advent of HAART, suggested that the course of HIV infection is accelerated in transplant patients, either because of the effect of immunosuppression on, or the role of alloantigenic stimulation in, HIV replication.…”
Section: Discussionmentioning
confidence: 99%
“…17 The primary concern is the potential side effects of immunosuppression after OLT and the effect it may have on HIV disease progression. [18][19][20][21][22][23][24] The conceptual conflict lies in the iatrogenic immunosuppression of an already immunosuppressed individual (i.e., an HIV-positive patient). Early reports, before the advent of HAART, suggested that the course of HIV infection is accelerated in transplant patients, either because of the effect of immunosuppression on, or the role of alloantigenic stimulation in, HIV replication.…”
Section: Discussionmentioning
confidence: 99%
“…This seems particularly likely because residual Vpr expression is detected even in CypA Ϫ/Ϫ Jurkat cells. Since Vpr supports virus replication, particularly in nondividing cells, and has been reported to sustain pathogenesis in SIV-infected monkeys (66), this accessory protein could form a target for the development of new anti-retroviral therapies. Several approaches have been reported that interfere with Vpr function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the first clinical studies using monotherapy with CsA in patients with chronic HIV-1 infection or at advanced stages of AIDS revealed only subtle beneficial effects of long term CsA treatment on preventing disease progression (70). In contrast, CsA treatment of rhesus monkeys acutely infected with SIV showed advantageous effects of CsA on antigenemia and loss of CD4 ϩ T cells (66). Further, it is well established that primary HIV infection is associated with massive immune activation, and it was shown recently (71) that this very critical period for initiation of highly active antiretroviral therapy can benefit from combining highly active antiretroviral therapy with CsA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For SIV, both virus-expressing cells and virionassociated viral RNA trapped on the surface of follicular dendritic cells were evaluated. Determination of the number of SIVexpressing cells and the amount of follicular dendritic cellsdeposited SIV RNA was achieved by image analysis of lymph-node sections, using a phosphorimager (Fuji Medical Systems, Burbank, CA), as described (40). In situ hybridization for HHV-6A RNA was performed by using as a probe in vitro RNA transcripts from molecular clone pZVH14, which encodes, among others, the large tegument protein (U31) (42).…”
Section: Methodsmentioning
confidence: 99%